2021
DOI: 10.1093/protein/gzab008
|View full text |Cite
|
Sign up to set email alerts
|

A fragment-based protein interface design algorithm for symmetric assemblies

Abstract: Theoretical and experimental advances in protein engineering have led to the creation of precisely defined, novel protein assemblies of great size and complexity, with diverse applications. One powerful approach involves designing a new attachment or binding interface between two simpler symmetric oligomeric protein components. The required methods of design, which present both similarities and key differences compared to problems in protein docking, remain challenging and are not yet routine. With the aim of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…The interfaces here could prove useful in constructing the structures of protein complexes or even building a whole protein structure from individually solved domains. Our library could also be used in conjugation with fragment based interface design algorithms such as nanohedra [71]. With the rapid growth of structures resolved using cryo-EM, a library such as ours could also prove useful in refining such structures.…”
Section: Discussionmentioning
confidence: 99%
“…The interfaces here could prove useful in constructing the structures of protein complexes or even building a whole protein structure from individually solved domains. Our library could also be used in conjugation with fragment based interface design algorithms such as nanohedra [71]. With the rapid growth of structures resolved using cryo-EM, a library such as ours could also prove useful in refining such structures.…”
Section: Discussionmentioning
confidence: 99%
“…Our library could also be used in conjugation with fragment-based interface design algorithms such as nanohedra. 86 With the rapid growth of structures resolved using cryo-EM, a library such as ours could also prove useful in refining such structures. The information presented in this study would soon be available as a queryable relational database on a webserver (work in progress).…”
Section: Discussionmentioning
confidence: 99%
“…The interfaces here could prove useful in constructing the structures of protein complexes or even building a whole protein structure from individually solved domains. Our library could also be used in conjugation with fragment‐based interface design algorithms such as nanohedra 86 . With the rapid growth of structures resolved using cryo‐EM, a library such as ours could also prove useful in refining such structures.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in protein engineering have enabled the bottom-up design of purpose-built protein nanoparticles, drastically expanding the protein nanoparticle design space. These methods typically apply principles of symmetry to arrange natural or de novo designed cyclic oligomers into protein nanoparticles through interface design or rigid genetic fusion, reviewed in Khmelinskaia, Wargacki, and King (2021). Padilla, Colovos, and Yeates et al (2001) reported an early example of a self-assembling protein nanoparticle constructed using the rigid fusion of several oligomeric domains . Recently computational protein design has been applied to interface and rigid fusion methods enabling the design of increasingly complex protein nanoparticles with improving success rates. ,, King and Baker et al (2012) reported self-assembling protein nanoparticles with a variety of symmetries using computational protein interface design to arrange existing cyclic oligomers into the desired assemblies (Figure B) .…”
Section: Part 1: Designable Features Of Protein Nanoparticlesmentioning
confidence: 99%